Oncolytic Viruses: Can be Applicable Tools for Cancer Therapy? - Shayestehpour, Mohammad (Journal of Current Viruses and Treatment Methodologies, 2018)
A concise review of oncolytic virotherapy covering viral engineering, tumor selectivity, and immune modulation. It assesses preclinical and clinical progress and discusses combinations with immunotherapies to enhance antitumor effects.
Keywords: Oncolytic Viruses; Cancer Therapy; Viral Engineering; Tumor Selectivity; Immune Modulation